Mempertahankan Sorga di Delang: Dilema Sawit dan Hutan - John Christianto Simon (Faculty of Theology Duta Wacana Christian University, 2016)
Abstract The ecological issue has become crucial and urgent problem to be responded the logically and practically. This very issue is inseparable from a challenge in the form of catastrophic convergence: poverty, injustice, and violence. Analysis on the ecological problem brought us to trace back the problem of thought contributed by certain philosophical and thelogical thought. It has given birth to an absolute anthropocentrism which has been consolidated by certain theology and in turn gave birth to an expansive notion by way of the mastery over nature, even over other human fellow. The absolutisation of ratio brought about the birth of capitalism (globalized imperialism), which in turn created man as homo oeconomicus in which its keyword is injustice. In the middle of the impoverishing massive ecological damage, there is a different story that showed a local community's ability in defending the environmental conservation. A small village, Kudangan, in Delang Subdistrict are in agreement